Earnings management para evitar reportar pérdidas: Chile, 2010-2014 - Edinson Edgardo Cornejo-Saavedra (Journal of Economics, Finance and Administrative Science, 2018)
This paper aims to examine whether a sample of non-financial Chilean firms performed earnings management to avoid the decreases and losses in the earnings during the 2010-2014 period. Design/methodology/approach The analysis is undertaken using the distributions of earnings changes and earnings, according to Burgstahler and Dichev (1997) methodology. Findings The results showed unusually low frequencies of small losses and small declines in earnings and unusually high frequencies of small benefits and small increases in earnings. Both results were statistically significant. Practical implications The study presents evidence of possible earnings management activity to avoid reporting losses and earnings decreases during the period 2010-2014. These results would allow to identify "suspicious" companies of earnings management and would increase the likelihood of detecting firms that managed upside the reported earnings or that - in an extreme case - would be committing a fraud not disclosed. Originality/value The results of these types of studies would be useful to carry out monitoring and control activities, to increase transparency in the stock market.
Keywords: 330; Earnings management; Losses; Earnings; Frequency distribution; Profit threshold